Disseminated intravascular coagulation - Venugopal, A (Medknow Publications & Media Pvt Ltd, 2014)
Disseminated intravascular coagulation (DIC) is a reflection of an underlying systemic disorder which affects the coagulation system, simultaneously resulting in pro-coagulant activation, fibrinolytic activation, and consumption coagulopathy and finally may result in organ dysfunction and death. Though septicaemia is the most common cause of DIC, several other conditions can also lead to it. A diagnosis of DIC should be made only in the presence of a causative factor supported by repeated laboratory tests for coagulation profile and clotting factors. An effective scoring system helps to detect an overt DIC and a high score closely correlates with mortality. Treatment of DIC is aimed at combating the underlying disorder followed by supportive management. Low molecular weight heparin is advocated in special situations whereas anti-thrombin III and activated protein C are of doubtful value. Early diagnosis and prompt treatment backed by laboratory support can reduce the morbidity and mortality associated with it. The methodology of search for this review article involved hand search from text books and internet search using Medline (via PubMed) using key words DIC, thrombosis, fibrin degradation products, anti-thrombin and tissue factor for the last 25 years and also recent evidence-based reviews.